2013
DOI: 10.1159/000355830
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Status of Antiganglioside Antibodies in Children with Guillain-Barré Syndrome

Abstract: Objective: Antiganglioside antibodies have been reported to play a role in the pathophysiology of Guillain-Barré syndrome (GBS). Methods: This case-control study was designed to evaluate the status of antiganglioside antibodies in children with GBS. The study included 50 patients suffering from GBS as the case group and 30 children as the control group. Clinical information such as demographic data and recent digestive or respiratory infection (within the last month) was collected for all patients, and paracli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The test accuracy varies depending on GBS subtype, tested antigen and control group. Anti‐GM1 IgG antibody sensitivity for the whole group of GBS patients ranges from 20% to 69% and varies between geographical regions 71–75,101 . Anti‐GM1 specificity is reported to be high (94%–98%) in GBS compared with healthy controls and other neurological diseases 25,54,73,102 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The test accuracy varies depending on GBS subtype, tested antigen and control group. Anti‐GM1 IgG antibody sensitivity for the whole group of GBS patients ranges from 20% to 69% and varies between geographical regions 71–75,101 . Anti‐GM1 specificity is reported to be high (94%–98%) in GBS compared with healthy controls and other neurological diseases 25,54,73,102 .…”
Section: Resultsmentioning
confidence: 99%
“…Evidence summary: Serum antibodies that have been tested in GBS cases include GM1, [71][72][73][74][75] GM1b, 76 GD1a, 77 GQ1b, [78][79][80][81][82][83] GalNAc-GD1a, [84][85][86] GT1a, 87 GD1b, GD3, O-GD3, GT3, O-GT3, 88 sulfatide, 89,90 galactocerebroside, 91,92 CNTN1, 93 NF155 and NF 186, 94,95 cardiolipin, 96 LM1, [97][98][99] sulphated glycolipids, 89 P0 and PMP22. 100 The test accuracy varies depending on GBS subtype, tested antigen and control group.…”
Section: Considerations Supporting the Gpps (Supporting Information)mentioning
confidence: 99%
“…Hashemilar et al. (2014) suggested that EUROLINE method could be used instead of the ELISA method except for the anti‐GQ1b antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence summary: Serum antibodies that have been tested in GBS cases include GM1, [71][72][73][74][75] GM1b, 76 GD1a, 77 GQ1b, [78][79][80][81][82][83] GalNAc-GD1a, [84][85][86] GT1a, 87 GD1b, GD3, O-GD3, GT3, O-GT3, 88 sulfatide, 89,90 galactocerebroside, 91,92 CNTN1, 93 NF155 and NF 186, 94,95 cardiolipin, 96 LM1, [97][98][99] sulphated glycolipids, 89 P0 and PMP22. 100 The test accuracy varies depending on GBS subtype, tested antigen and control group.…”
Section: Considerations Supporting the Gpps (Supporting Information)mentioning
confidence: 99%